Simultaneous Method Development and Validation of Esomeprazole and Domperidone in Pure and Pharmaceutical Dosage Forms By RR-HPLC - ROOSEWELT, C.; MAGESH, AR.; RAVISUDAR, A.; SHANMUGA PANDIAN, P.; MUTHUPRASANNA, P.; GUNASEKARAN, V. (Asian Journal of Chemistry, 2010)
A simple, precise RP-HPLC method was developed for the estimation of esomeprazole and domperidone in pure and pharmaceutical dosage forms. The quantification was carried out using a C-18 column 250 × 4.6 mm i.d, 5 μm particle size in isocratic mode, with mobile phase comprising of buffer and acetonitrile in the ratio of 62:38 (v/v) pH 4.5. The flow rate was 1 mL/min and the detection was carried out by UV detector at 220 nm. The retention times were 6.308 and 7.425 min for esomeprazole and domperidone, respectively. The method produced linear response in the concentration range of 200-1000 μg/mL for esomeprazole and 100-500 μg/mL for domperidone. The percentage recovery was found to be 99.98 and 98.95 % for esomeprazole and domperidone, respectively. The method was validated by evaluation of required parameters.